The development of health care legislation in Malaysia: an overview - Anisah Che Ngah; Azlinda Baroni; Zaleha Abdullah Mahdi (Fakulti Undang-undang, Universiti Kebangsaan Malaysia, 2017)
This article will trace the development of health care legislation in Malaysia since its inception in 1957. Throughout the years, healthcare has continued to be the primary responsibility of the government with careful and precise planning translated into a document known as the Malaysian Plan (1967-2020). In these Malaysian Plans, serious attention and effort have been given towards the progress and success of health care in Malaysia thus, giving the backdrop for the health care system in the country. Further, healthcare regulations and policies are drafted to ensure compliance and provide safe healthcare to every individual who accesses the system. These regulations are developed and implemented at all levels of government namely federal, state and local authorities. The authors used the content analysis methodology to scrutinize legislative documents and government guidelines and policies on health care. Findings suggest that although Malaysia has achieved its objective considerably in health care, it is facing challenges in keeping up with the new demands of the current societal needs in the health care industry hence, health care legislation must follow suit.